2008
DOI: 10.1111/j.1365-3040.2008.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals elevated CO2 and elevated O3 alter resistance of soybean (Glycine max) to Japanese beetles (Popillia japonica)

Abstract: The accumulation of CO2 and O3 in the troposphere alters phytochemistry which in turn influences the interactions between plants and insects. Using microarray analysis of field-grown soybean (Glycine max), we found that the number of transcripts in the leaves affected by herbivory by Japanese beetles (Popillia japonica) was greater when plants were grown under elevated CO2, elevated O3 and the combination of elevated CO2 plus elevated O3 than when grown in ambient atmosphere. The effect of herbivory on transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 65 publications
3
70
0
Order By: Relevance
“…Transcriptional changes involved in flavonoid and isoflavonoid biosynthesis supported our findings that abundance increased after beetle damage (e.g., putative flavonol synthase, 2′-hydroxydihydrodaidzein reductase, isoflavone reductase-like protein), with or without elevated CO 2 , and increased flavonol biosynthesis (e.g., flavonol synthase-like oxidoreductase) under elevated CO 2 conditions (Casteel et al 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Transcriptional changes involved in flavonoid and isoflavonoid biosynthesis supported our findings that abundance increased after beetle damage (e.g., putative flavonol synthase, 2′-hydroxydihydrodaidzein reductase, isoflavone reductase-like protein), with or without elevated CO 2 , and increased flavonol biosynthesis (e.g., flavonol synthase-like oxidoreductase) under elevated CO 2 conditions (Casteel et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…In a separate study, tissue from plants in the beetle treatments from this experiment was examined via microarray to investigate transcriptional responses to elevated CO 2 and leaf skeletonization (Casteel et al 2008). Transcriptional changes involved in flavonoid and isoflavonoid biosynthesis supported our findings that abundance increased after beetle damage (e.g., putative flavonol synthase, 2′-hydroxydihydrodaidzein reductase, isoflavone reductase-like protein), with or without elevated CO 2 , and increased flavonol biosynthesis (e.g., flavonol synthase-like oxidoreductase) under elevated CO 2 conditions (Casteel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…An extension of this approach has recently been demonstrated in a microarray analysis of field-grown soybean (Glycine max), in which it was shown that the number of transcripts in the leaves affected by herbivory by Japanese beetles (Popillia japonica) was greater when plants were grown under elevated CO 2 , elevated O 3 and the combination of elevated CO 2 pluselevated O 3 than when grown in ambient atmosphere (Casteel et al, 2008). Interestingly, expression of a GLP sequence (Affymetrix IDGma.15727.1.S1 at) was reduced in response to insect damage.…”
Section: E Insectsmentioning
confidence: 97%
“…Moreover, the progressive inhibitors of the activity of enzymes of nitrogen metabolism, NiR and GDH, were two other key genes in our study. Some researchers have reported that NiR is up-regulated in soybean [37] and GDH is changed in paper birth [36] under elevated CO 2 . In addition, the key gene AS plays an important role in amino-acid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%